Effectiveness of Secondary Alveolar Bone Graft on Canine Eruption: Systematic Review - Lacerda-Santos, Rogério; Batista, Rhaslla Gonçalves; Neves, Samantha Silva; Araújo, José Lucas dos Santos; Vieira, Rayssa Amaral; Carvalho, Fabiola Galbiatti de; Pithon, Matheus Melo; Martins, Carolina de Castro (European Journal of Dentistry, 2021)
There are controversies related to the effects of bone grafts on tooth eruption and impaction in patients with cleft lip and palate. The aim of this systematic review was to evaluate the effectiveness of bone grafting on eruption of canines in patients with unilateral cleft lip and palate (UCLP). An electronic search was conducted in six electronic databases and gray literature, without limitations on year of publication or language. The primary outcome was the increase in rate of canine eruption; the secondary outcomes were success of the bone graft, canine impaction due to agenesis of the lateral incisor, and effect of orthodontic treatment before and after bone grafting. The risk of bias was analyzed by means of the tool Cochrane risk of bias in nonrandomized controlled trials (NRCTs) of interventions (ROBINS-I). The certainty of the evidence was assessed for outcomes reported through a narrative synthesis using grading of recommendations, assessment, development and evaluation (GRADE) approach. Four NRCTs were included, with a total of 360 patients, 283 UCLP and 77 bilateral cleft lip and palate (BCLP). The studies reported association between the increase in the rate of tooth eruption and bone graft with very low certainty of evidence, and greater experience of surgical success, with low certainty of evidence. The majority of the studies found an association between increase in the rate of canine impaction and agenesis of the lateral incisor, with very low certainty of evidence. There was very low certainty of the efficacy of secondary alveolar bone grafting for increasing the rates of eruption and reducing impaction of the maxillary canine.
Keywords: cleft palate; alveolar bone grafting; tooth eruption; systematic review